Ubuntu and Violence - Matolino, Bernard (African studies (Johannesburg), 2025)
Ubuntu in its essential outlook is committed to a humane and conciliatory interchange between moral agents and their environs. Yet the countries that have given ubuntu its name have had violence at the centre of their public spaces. This raises the question: what sort of engagement could there be between the violence inherent in these countries and ubuntu? And to what end would that engagement be? I examine ubuntu's relationship with violence, looking at the enduring effects of the historical reality of the banality of the violence of oppression. In the second instance, I seek to demonstrate how ubuntu, which is characteristically postcolonial, has developed an identity that is antithetical to ubuntu. The routine production of these disasters, and the normalcy of the existence of absurdity that generates violence of all sorts, has become the sign and mode of modern postcolonial Africa. This identity appears intransigent. In the light of these two instances, I seek to explore what aspects of ubuntu render it unable to shape its home turf.